Reputation Management in Complex Environments—A Comparative Study of University Organizations. Issue 1 (March 2017) - Christensen, Tom; Gornitzka, Åse
Abstract The times are long gone when universities were closed entities dominated by a selected group of professors. Modern universities cater to a wide variety of stakeholder groups and are hence socially embedded: they provide information, project an image of themselves, and are connected in different ways to actors in the environment who are important providers of resources, support, commitment, trust, and legitimacy. Reputation management is therefore important. We ask what is typical for the reputation management of universities? What are the core symbols and how are different types of symbols balanced? How much do universities focus on their performance record, their moral symbols (openness, trust, caring, etc.), and professional qualities? We set out to answer these questions using a comparative analysis of twenty universities in four Nordic countries. The data consist of a web census — a systematic analysis of the websites of the universities in question.